Emergency Quick Releasing Mechanism with Spring Linkage and Performance Analysis of the Vehicle Door Latch - Zhang Jiale; Hang Lubin; Zhong Chuanlei; Huang Xiaobo; Liu Zhe; Chen Yong (Jixie chuandong)
In view of the demand for quick releasing of the side door latch of an automobile in an emergency, an emergency quick releasing mechanism based on spring linkage is proposed. Based on the singular configurations, the contact states of ratchet and pawl and the limit contact states, the variable topology and multiple motion modes of the emergency releasing branch chain under different working conditions are studied. The necessary conditions for emergency releasing are obtained by the static analysis. The feasibility of quick releasing of emergency releasing branch chain in door latch is verified by the Adams software simulation. The control variable method is used to study the releasing time and the consistency of the releasing time of the emergency branch chain. When the stiffness of the main spring is within 5-7 N/mm and the preload is within 75-85 N, the maximum energy storage position of the main spring has a small offset, which meets the consistency of the releasing time. The emergency quick releasing mechanism based on the spring linkage is embedded in the side door lock of the car, meeting the requirements of small releasing force, high priority and releasing time, and providing important theoretical basis and practical value for the design and performance optimization of emergency quick releasing branch chain.